(untitled) (Journal of Science, Technology and Innovation Policy, 2023)
Workplace harassment exists throughout all types of workplaces. This is also experienced in developed countries, developing countries and undeveloped countries all over the world. Harassment is a type of bullying and discrimination and considered as a social problem. It is important for all workers to understand workplace harassment so you can avoid a hostile work environment. A good workplace harassment policy must be implemented and regulated so that the necessary steps can be taken so ensure a safe working environment for all employees. Most basic types of harassment are verbal and psychological; there are also more serious forms, such as abuse, physical and sexual. All types of workplace harassment are considered illegal. They will not only affect an employee’s productivity, comfort and safety at work, but they can also expose an organization to legal liability if it does not handle the harassment properly. Sexual harassment is a widespread and global problem that affects both women and men. Women and girls however, more commonly experience it, across all levels of society around the world. The global movement that went viral in October 2017 started out as a social media hash tag, the movement has since massively grown, encouraging millions of women across the world to speak out about sexual harassment. The Malaysian pledge to uphold the success of Sustainable Development Goals (SDG) on Gender Equality and Health and Well Being is also interconnected with the topic above, so implementing related laws/policies on work place and sexual Harassment with intervention from the Government is crucial to reduce and mitigate the social problem. This assignment will focus on government intervention to address such problems by implementing / establishing laws, policies, code of conduct practices and guidelines to protect women in the workplace. I will use case studies from South Korea, Malaysia and Cambodia to try to find similar programs that have been implemented to protect the rights of women in the workforce as equal humans. By then, researcher will be able to prove that through workplace harassment law/policies will make it way to reduce the harassment problem.